Falling terrorism and rising conflicts the Afghan "Contribution" to polarization and confrontation in West and South Asia - Peimani, Hooman 1957- (Praeger, 2003)
Analyzes the long-term impact of the fall of the Taliban not only on Afghanistan, but also on the South and West Asia regions.